Connecting the dots: A longitudinal observation of relief organizations' representational networks on social media. (September 2017) - Lai, Chih-Hui; She, Bing; Tao, Chen-Chao
Abstract: In response to the call in the public relations research to examine organizations' relationship building beyond dyadic organization-public ties, this study employs a multidimensional network approach to understand relief organizations' relationship building through different features of social media. Unlike the organizations studied in the existing public relations research, relief organizations often incorporate emergency or disaster response as part of their mission operations. Specifically, this study focuses on the organizations involved in the response actions after Typhoon Haiyan. Analysis of 66 relief organizations' network data on Twitter and Facebook shows that organizations' multiple types of relationships in the form of interorganizational representational networks constructed through different features of social media are closely linked during and immediately after Typhoon Haiyan. However, organizations' positional centrality stays persistent across these networks over time, which suggests both constraints and opportunities for organizations to build relational advantages through distinct features of social media. Findings of this study show the usefulness of a multidimensional network approach in revealing the hidden patterns behind organizations' communication behavior on social media. In doing so, this study offers more comprehensive explanations for organizations' relationship building and relational outcomes through social media use. Highlights: A multidimensional network view is employed to examine relief organizations' social media use. Representational networks reflecting organizations' use of Twitter and Facebook were analyzed. Multiple interorganizational representational networks are correlated during the disaster. Organizations' positional advantages are maintained across interorganizational networks. Circumstances for organizations' cross-platform strategic communication are revealed.